2002
DOI: 10.1007/s00167-002-0302-2
|View full text |Cite
|
Sign up to set email alerts
|

A correlation study of objective functionality and WOMAC in total knee arthroplasty

Abstract: Function studies after total knee arthroplasty (TKA) generally use either self-reported instruments or objective quantitative measurements of walking activities, but it is unclear how objective factors influence self-reports. This retrospective multicenter study assessed the impact of objective variables on subjective self-reported functional outcome after TKA in 128 patients at a mean of 41 months after TKA. Self-reported disability was measured by the Western Ontario and McMaster University (WOMAC) scale, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…To this end, discordance between the KOOS ADL subscale score and performance-based measures of important daily activities such as gait and stairs climbing has been previously reported. 46-48 Therefore, determining which particular activities of daily living are deemed problematic by patients with different pain patterns would be a valuable indicator of current and future functional status in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, discordance between the KOOS ADL subscale score and performance-based measures of important daily activities such as gait and stairs climbing has been previously reported. 46-48 Therefore, determining which particular activities of daily living are deemed problematic by patients with different pain patterns would be a valuable indicator of current and future functional status in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies 41,51 released in the conception period of this study had demonstrated generally low associations between self-report and performance measures on outpatients with similar orthopaedic conditions, there were reasons to examine their relationships on inpatients. Self-report measures of function were conceived to assess function, and, as they are increasingly being used in research, 2 it is important to understand how well performance is actually represented by these measures at different phases of rehabilitation.…”
mentioning
confidence: 94%
“…Results of this study are consistent with these findings. 16,41,43,51 The ICF 52 is a framework that may help to explain the low correlations between the LEFS and the comparison measures. Although the acts/task assessed in the LEFS, the TUG, and the TLFIM all belong to the "Mobility" chapter under the "Activities and Participation" component of the ICF, 53 the environmental and personal factors that likely interact with these tasks are not being considered equally in these 3 measures.…”
mentioning
confidence: 99%
“…This investigation further sought to evaluate the relationship between changes in HOOS pain and ADL subscale scores. Based on findings from other arthroplasty populations, 7,18,19,20 it was hypothesized that changes in HOOS pain and ADL subscale scores would be significantly correlated.…”
Section: Introductionmentioning
confidence: 99%